The Supremacy of Patient Safety: Juridical and Empirical Analysis of Emergency Medical Care - Sari, Novia Eka; Fikri , Ahmad Ma’mun (Research Horizon, 2025)
The principle of Aegroti Salus Lex Suprema (Patient Safety is the Supreme Law) forms the ethical and legal core of healthcare, strictly prohibiting the refusal of patients in emergency conditions, as codified in the Indonesian Health Law, Law Number 17 of 2023. However, documented cases show a persistent gap between this legal mandate and clinical reality, often due to administrative priorities. This study aims to explicitly examine the legal foundation of the Aegroti Salus Lex Suprema principle and to analyze its concrete implementation. This study employs a sociological-juridical approach with a case study methodology to analyze the legal basis and the concrete implementation of this principle in emergency practice. Primary data, collected via interviews and observation, supplemented by secondary legal materials, were analyzed qualitatively. Findings indicate that this Islamic hospital institutionalizes Aegroti Salus Lex Suprema through rigorous internal regulations, including staff credentialing, establishing a maximum 5-minute response time, implementing triage protocols, and creating detailed resuscitation guidelines. The study concludes that this Islamic hospital successfully fulfills its social and legal duty by embedding patient safety as the highest institutional priority, providing a strategic model for minimizing malpractice risks and enhancing life-saving accountability across Indonesian healthcare facilities.